Dryland Crops Program: Tackling the 50:20 challenge - Pixley, Kevin V.; Gandhi, Harish; Ojiewo, Chris O. (International Maize and Wheat Improvement Center, 2025)
In 2024, CIMMYT’s Dryland Crops Program (DCP) laid the foundations to advance its vision and address the 50:20 challenge. This is possible through the efforts of over 200 scientists from partner institutions, working collaboratively to deliver impact.